Quiste hemorrágico del Nervio Oculomotor: Video microquirúrgico de una patología infrecuente - Bottan, Juan S; Rubino, Pablo A; Salas López, Eduardo; P. Arévalo, Román; De Oliveira, Evandro (Revista Argentina de Neurocirugía, 2020)
Introduction: Intracranial Intraneural cysts a rare pathology and have only being barely described in the literature,1 mostly associated to the oculomotor nerve. Ethology is unknown, and the few cases shared in previous publications present with acute clinical onset, and usually associated with hemorrhage. These lesions are subject to differential diagnosis with arachnoidal cysts2-7 parasellar tumors and aneurysms.8-10 We present a surgical video of an intracranial intraneural hemorrhagic cyst of the third nerve. Case presentation: A 77-year-old male with a 6-month history of a complete left third nerve palsy. CT and MRI scans showed a cystic-like lesion in the parasellar region, medially-adjacent to the left uncus. A “level sign” suggested a hemorrhagic event. Differential diagnosis with a cerebral aneurysm was obtained by Angio CT and digital angiogram, which didn’t show any vascular abnormalities. Exploratory surgery was proposed. A Left-sided standard pterional craniotomy was performed, and a large purely intraneural cyst with a hemorrhagic liquid content was observed. The cyst was successfully fenestrated and inspected, and third nerve integrity could be maintained. Unfortunately, no samples for pathology could be obtained. After a 6 month-postoperative period, the patient has recovered full extrinsic and intrinsic function, with no diplopia. However, a moderate ptosis persisted. Conclusion: The video shows the most relevant technical aspects of the procedure, including the microsurgical dissection of the lesion and the inspection of the cyst and oculomotor nerve in such a rare pathology.